Head and neck carcinoma and its association with environmental factors - Kumar, Brijesh; Shukla, Anirudh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cancer of head and neck are the 6th most common cancer worldwide, with an increasing frequency in developing countries. In India head and neck cancers account for 30-40% cancer at all sites. Head and neck cancers are one of the major causes of morbidity and mortality in older age groups. The lack of awareness, unavailability of proper screening facilities in rural population and use of carcinogenic addiction are the cause for high prevalence of cancer of head and neck in developing countries. Methods: This cross-sectional study on head and neck carcinoma and its association with environmental factors was carried out in the Department of Otorhinolaryngology and Head- Neck surgery, N. S. C. B. MCH, Jabalpur from January 2016 to January 2017. Results: The prevalence is found to be significantly high in carcinoma oral cavity which is 45.5% followed by carcinoma larynx (30%). These are affecting male more than female with ratio of 6:1, in the age group of 4th to 6th decade, living in low socioeconomic strata. Majority are associated with tobacco chewing (33.3%) followed by smoking (25.5%). Conclusions: It is concluded that patients usually present to a tertiary care centre at advanced stages. This can be attributed to lack of awareness and unavailability of proper medical facilities in rural population. There should be awareness about disease, health education in community about carcinogenic substances like tobacco, smoking, alcohol etc., proper medical facilities in low socioeconomic strata to reduce the burden of carcinomas.